A Structural Model of Truncated Gaussia princeps Luciferase Elucidating the Crucial Catalytic Function of No.76 Arginine towards Coelenterazine Oxidation. - Nan Wu; Zhi-Chao Xu; Kai-Dong Du; Shen Huang; Naohiro Kobayashi; Yutaka Kuroda; Yan-Hong Bai (PLoS Computational Biology)
Gaussia Luciferase (GLuc) is a renowned reporter protein that can catalyze the oxidation of coelenterazine (CTZ) and emit a bright light signal. GLuc comprises two consecutive repeats that form the enzyme body and a central putative catalytic cavity. However, deleting the C-terminal repeat only limited reduces the activity (over 30% residual luminescence intensity detectable), despite being a key part of the cavity. How does the remaining GLuc (tGLuc) catalyze CTZ? To address this question, we built a structural model of tGLuc by removing the C-terminal repeat from the resolved structure of intact GLuc, and verified that the cavity-forming component in GLuc remains stable and provides an open-mouth cavity in tGLuc during 500 ns MD simulations in water. Docking simulation and a followed umbrella sampling analysis further revealed that the cavity on tGLuc has a high affinity for CTZ, with a binding energy of up to -114 kJ/mol. Moreover, R76, a validated activity-critical amino acid residue, resides in the cavity and forms a stable hydrogen bond with CTZ. Then, we constructed a cluster model to examine the CTZ oxidation pathway in the cavity using Density Functional Theory (DFT) calculations. The result showed that the pathway consists of four elementary reactions, with the highest Gibbs energy barrier being 65.4 kJ/mol. Both intramolecular electron transfer and the convergence of S1/S0 potential energy surfaces occurred in the last elementary reaction, which was regarded as the reported Chemically-Initiated-Electron-Exchange-Luminescence (CIEEL) reaction. Geometry and wavefunction analysis on the pathway indicated that R76 plays a vital role in CTZ oxidation, which first anchors the environmental oxygen molecule and induces it to form a singlet biradical state, facilitating its attack on CTZ. Subsequently, R76 and the adjacent Q88, positioned near R76 through the tGLuc refolding process, stabilize the transition states and facilitate the emergence of radical electrons on CTZ at the onset of the CIEEL reaction, which contributes to the subsequent intramolecular electron transfer and the production of excited amide product. This study provides a comprehensive explanation of tGLuc's catalytic mechanism. However, it is important to note that these findings are specific to tGLuc and may not extend to other CTZ-based luciferases, particularly those lacking arginine in their catalytic cavities, which likely operate via distinct mechanisms.